1999
DOI: 10.1063/1.371301
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and giant magnetoimpedance of nanocrystalline Fe92−xZr7BxCu1 ribbons

Abstract: The influence of substitution of B for Fe on the microstructure, magnetic properties, and giant magnetoimpedance (GMI) effect has been studied for the nanocrystalline soft magnetic ribbons Fe92−2Zr7BxCu1 (x=2,4,6,8,10) annealed at 873 K for 20 min. The experimental results show that the thermal stability of the amorphous precursor is enhanced and the body-centered-cubic phase grains become smaller with increasing B content. The coercive force Hc exhibits a minimum of 2.51 A/m for the ribbon with x=8, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Many previous research results have confirmed that maximum MI ratio increases with increasing driving frequency, and then decreases when frequency excesses some a critical value [29,30]. The decrease of MI effect at high frequencies is due to the strong suppression of the domain wall movement by eddy current effect, which causes an extreme decrease of permeability [29,[31][32][33]. As the highest frequency can only reach 1110 kHz under our experimental conditions, we are unable to give full Z/Z(%) max -frequency curves for Co 72 Zr 8 B 20 in the as-quenched state and annealed at 495 • C. In many cases, with increasing frequency the MI effect increases due to involvement of the rotational processes.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Many previous research results have confirmed that maximum MI ratio increases with increasing driving frequency, and then decreases when frequency excesses some a critical value [29,30]. The decrease of MI effect at high frequencies is due to the strong suppression of the domain wall movement by eddy current effect, which causes an extreme decrease of permeability [29,[31][32][33]. As the highest frequency can only reach 1110 kHz under our experimental conditions, we are unable to give full Z/Z(%) max -frequency curves for Co 72 Zr 8 B 20 in the as-quenched state and annealed at 495 • C. In many cases, with increasing frequency the MI effect increases due to involvement of the rotational processes.…”
Section: Resultsmentioning
confidence: 71%
“…5 that no MI response is obtained in the sample annealed at 630 • C at any of the measuring frequencies. Many previous research results have confirmed that maximum MI ratio increases with increasing driving frequency, and then decreases when frequency excesses some a critical value [29,30]. The decrease of MI effect at high frequencies is due to the strong suppression of the domain wall movement by eddy current effect, which causes an extreme decrease of permeability [29,[31][32][33].…”
Section: Resultsmentioning
confidence: 79%
“…The initial increase in the MI values is assigned to decrease the skin effect, which causes the transverse permeability to increase resulting in a net increase in magnetoimpedance. The decrease in MI values at higher frequencies than 5 MHz is caused by the damping wall motion as an outcome of eddy currents around domain walls [14]. MIR curves measured at 5 MHz as a function of the applied field for the samples with composition Co 64 Fe 4 Ni 2 B 18 Si 8 Cr 3 Al 1 at different quenching rates is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The initial increase in the MI values is attributed to decrease in skin effect which causes the transverse permeability to increase resulting in a net increase in magnetoimpedance. The decrease in MI values at higher frequencies is due to the damping of domain wall motion as a result of eddy currents around domain walls [20]. Fig.…”
Section: Structural Characterizationmentioning
confidence: 93%